Management and outcomes of spinal epidural hematoma during vertebroplasty: Case series. Issue 21 (May 2018) - Fang, Miao; Zhou, Jiaojiao; Yang, Dongjun; He, Yu; Xu, Yong; Liu, Xin; Zeng, Yong
Abstract: Rationale: Spinal cord injury (SCI) is one of the common complications of spinal surgery. There is no definite treatment and time of decompression for spinal cord induced by epidural hematoma during vertebroplasty. Patient concerns: A total of 6 patients with SCI during vertebroplasty were included in our research. All of them occurred sensory disturbance and motor dysfunction due to a lower or same level operative vertebral body lesion in vertebroplasty. Diagnoses: Neurological manifestations during vertebroplasty, postoperative magnetic resonance imaging and computed tomography. Interventions: Once SCI occurred in vertebroplasty, four patients were underwent spinal cord decompression immediately, and two patients were done after 14 and 22 hours, respectively. Outcomes: Before decompression operation, one patient was Frankel A, three were Frankel B, and two were Frankel C. One day after evacuation of the SEH, three patients recovered to normal neurological function (Frankel E), one to Frankel C, and one to Frankel D, but the other one did not recover. At the last follow-up, five patients had recovered to Frankel E and one patient to Frankel D. Lessons: According to our experience, when SCI occurs during vertebroplasty, neurological deficits are always secondary to acute SEH. Timely decompression, particularly transfer surgery, can shorten recovery time.